Determine the origin of tidal oscillations in the ionospheric transition region with EISCAT radar and global model data - Günzkofer, Florian Ludwig; Pokhotelov, Dimitry; Stober, Gunter; Liu, Huixin; Liu, Hanli; Tjulin, Anders; Borries, Claudia (2022)
Vergleich von 24h und 12h Periodizitäten in thermosphärischen Winden mit Radarmessungen und Simulationsmodellen